2020
DOI: 10.3390/su12041322
|View full text |Cite
|
Sign up to set email alerts
|

Deltas in Crisis: From Systems to Sophisticated Conjunctions

Abstract: In recent years, threatened deltas have emerged as a significant matter of concern in numerous fields. While Earth System science and social-ecological systems focus on topics like global water circulation and sediment transport, social scientists tend to consider the problems facing particular deltas in the context of modernization or (post)-colonial development. There is nevertheless broad agreement that the delta crisis raises fundamental questions about modern approaches to infrastructure planning. Thus, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Thus, we end by highlighting our favored enactment of prek(s) as a profoundly networked socionatural mosaic, where numerous human and more-than-human beings are provided with generous opportunities for living together. Emphasizing the possibility of "conjunctions" (Jensen and Morita, 2020;Yates et al, 2017) that "interfere with modernity" (Choi, 2020), this ontological politics, we suggest, has implications for environmental knowledges and delta management far beyond the gates that dot Kandal's landscape.…”
Section: Encountering the Prek(s)mentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, we end by highlighting our favored enactment of prek(s) as a profoundly networked socionatural mosaic, where numerous human and more-than-human beings are provided with generous opportunities for living together. Emphasizing the possibility of "conjunctions" (Jensen and Morita, 2020;Yates et al, 2017) that "interfere with modernity" (Choi, 2020), this ontological politics, we suggest, has implications for environmental knowledges and delta management far beyond the gates that dot Kandal's landscape.…”
Section: Encountering the Prek(s)mentioning
confidence: 81%
“…This means engaging prek(s) as far more decentered and encompassing ways than enactments that reduce the landscape to a grid-type network of channels. It means embracing the scalar potentials of ontological pluralism (Jensen and Morita, 2020, Yates et al., 2017). Beyond irrigation and agricultural intensification, we are thus interested in scaling-up prek(s) as a socionatural mosaic .…”
Section: Room For Other Enactments?mentioning
confidence: 99%
“…Regulating and controlling groundwater extraction is needed to avoid subsidence, groundwater salinisation and the accumulation of pollution. 24: Garschagen et al ( 2011 ), 4 & 23: Hossain et al ( 2017 , 2020 ), 50: Jensen and Morita ( 2020 ) 74/75: Kumar et al ( 2020 ), 8-12: Renaud et al ( 2013 ), 13: Hoan et al ( 2019 ), and 52: Sherin et al (2020) Regulating land use to avoid smallholders’ land loss and enhancing the protection and conservation of ecosystems through policies is needed to reduce industrial forcing on landscapes. Developing effective measures of habitat protection must be planned in regard of communities’ livelihoods.…”
Section: Recommendationsmentioning
confidence: 99%
“…24: Garschagen et al ( 2011 ), 4 & 23: Hossain et al ( 2017 , 2020 ), 50: Jensen and Morita ( 2020 )…”
Section: Recommendationsmentioning
confidence: 99%
“…
Towards a deltaic lensLife in river deltas has become a matter of global concern. Threatened by rising sea levels and subsiding surfaces, starved of sediments and susceptible to extreme weather events, trapped in disadvantageous economies and governed by unaccountable, often postcolonial administrations, deltas and their inhabitants are known to be in crisis (Jensen and Morita 2020; Nicholls et al 2020). Propounding insights into the lives of delta inhabitants around the world, this book has shown that these people are indeed struggling on various fronts, yet signifi cantly, these fronts do not easily align with the dimensions of the global delta crisis.
…”
mentioning
confidence: 99%